Rhetorical Structure of Method Sections of Postgraduate Thesis in English Education Study Program Students - Abdullah Azzam An-Nashir; Syafryadin Syafryadin; Azwandi Azwandi (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
The method section of a thesis is crucial because it conveys the information upon which the study's validity is ultimately evaluated. The method section describes the procedure, instruments, design, data acquisition, and data analysis, among other components. Students may encounter several obstacles when composing a thesis, including the rhetorical issue. This study examines the rhetorical structure of the methodology section of a graduate thesis. This investigation employed a fundamental content analysis with quantitative methodology. The data was collected from 50 English education postgraduate theses at the University of Bengkulu. The results indicate that five Moves occurred in the thesis with varying frequencies. Moves 2, 3, and 4 occur most frequently, followed by Move 5, with Move 1 occurring least frequently. Furthermore, this research presents fifteen communicative purposes as Steps. 2 Steps are Obligatory (M2S1 and M3S2), 5 Steps are Conventional (M2S2, M2S3, M3S3, M4S1, M4S2), 7 Steps are Optional (M1S1, M3S1, M4S3, M5S2, M5S3, M5S4, M5S5), and 1 Step is non-obvious (M5S1). In conclusion, this study provides information about the rhetorical structure of the method sections of a thesis in order to heighten students' awareness of the significance of the three Obligatory movements in the method section. Students can use the framework or model presented in this study to present important information and construct a strong argument in the methodology section.